The Significance of Insecure and Disorganized Attachment for Children's Internalizing Symptoms: A Meta-Analytic Study - Groh, Ashley M.; Roisman, Glenn I.; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.; Fearon, R. Pasco (Child development, 2012)
This meta-analytic review examines the association between attachment and internalizing symptomatology during childhood, and compares the strength of this association with that for externalizing symptomatology. Based on 42 independent samples (N = 4,614), the association between insecurity and internalizing symptoms was small, yet significant (d = 0.15, CI 0.06~0.25) and not moderated by assessment age of internalizing problems. Avoidance, but not resistance (d = 0.03, CI - 0.11~0.17) or disorganization (d = 0.08, CI - 0.06~0.22), was significantly associated with internalizing symptoms (d = 0.17, CI 0.03~0.31). Insecurity and disorganization were more strongly associated with externalizing than internalizing symptoms. Discussion focuses on the significance of attachment for the development of internalizing versus externalizing symptomatology.